Android tablets for dummies - Gookin, Dan (--For dummies., 2013)
With Gookin's helpful advice, you can train your Android tablet to do you bidding. From using the address book and navigation system to making phone calls and video chats, this guide has solutions to common problems, as well as information on protecting your tablet and securing your data.